2018
DOI: 10.1002/lt.24965
|View full text |Cite
|
Sign up to set email alerts
|

Can negligible hepatic steatosis determined by magnetic resonance imaging–proton density fat fraction obviate the need for liver biopsy in potential liver donors?

Abstract: The purpose of this study is to determine whether magnetic resonance (MR)-proton density fat fraction (PDFF) estimate of negligible hepatic fat percentage (<5%) can exclude significant hepatic steatosis (≥10%) in living liver donor candidates obviating the need for liver biopsy and to perform intraindividual comparisons between MR-PDFF techniques for hepatic steatosis quantification. In an ethics-approved retrospective study, 144 liver donor candidates with magnetic resonance spectroscopy (MRS) and 6-echo Dixo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Kang et al[18] also found that the correlation in the right lobe was higher than that in the left lobe. Satkunasingham et al[19] conducted a retrospective study on liver donor candidates with liver biopsy as a reference; the researchers demonstrated a significant correlation ( r = 0.83) between ME Dixon and MRS (HISTO), and they showed that these two methods could obviate the need for liver biopsy when proton density fat fraction (PDFF) was < 5%. Furthermore, Bannas et al[20] performed MRI, MRS, liver biopsy, and biochemical triglyceride extraction on ex vivo human livers that were unsuitable for transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al[18] also found that the correlation in the right lobe was higher than that in the left lobe. Satkunasingham et al[19] conducted a retrospective study on liver donor candidates with liver biopsy as a reference; the researchers demonstrated a significant correlation ( r = 0.83) between ME Dixon and MRS (HISTO), and they showed that these two methods could obviate the need for liver biopsy when proton density fat fraction (PDFF) was < 5%. Furthermore, Bannas et al[20] performed MRI, MRS, liver biopsy, and biochemical triglyceride extraction on ex vivo human livers that were unsuitable for transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of Liver Transplantation , Satkunasingham et al compared MRI‐based estimations of hepatic steatosis to liver biopsy in 32 living donor candidates . Specifically, the MRS‐PDFF and 6‐echo Dixon MRI (MRI‐PDFF) were evaluated in their ability to discriminate between candidates with clinically significant histologic steatosis of ≥10%.…”
mentioning
confidence: 99%
“…These thresholds have been used in several studies as inclusion criteria for liver transplantation and for therapeutic trials. [46][47][48] Last, both UDFF and PDFF were compared to the body mass index (BMI) by computing the slopes of regression and 95% CIs versus BMI.…”
Section: Discussionmentioning
confidence: 99%
“…An additional receiver operating characteristic analysis was performed to evaluate the performance of UDFF for identifying steatosis defined as MRI‐PDFF higher than 5% or 10%. These thresholds have been used in several studies as inclusion criteria for liver transplantation and for therapeutic trials 46–48 . Last, both UDFF and PDFF were compared to the body mass index (BMI) by computing the slopes of regression and 95% CIs versus BMI.…”
Section: Methodsmentioning
confidence: 99%